Alternative Yoga Exercise on Fasting Blood Glucose and Cholesterol Levels among Patients with Type 2 Diabetes Mellitus - Vidya Urbaningrum Urbaningrum; Rr. Sri Endang Pujiastuti; Supriyana Supriyana (Alta Dharma Publisher, 2021)
Diabetes mellitus is a public health problem. The study used systematic literature reviews (SLR), which is a synthesis of a systematic literature study that is clear, comprehensive, by identifying, analyzing, evaluating through the collection of existing data with an explicit search method and involving the processes that have been critical in the selection of studies. The results found that 20 relevant articles have been reviewed and showed most of the evidence was significant on reducing fasting blood sugar and cholesterol levels. One study was not substantial on lowering cholesterol levels. Those 19 review studies showed that the study was a good category with an effect size value was 1.99 (robust) and a good JBI value. This was due to giving yoga interventions or the methods used during the training process is appropriate following the standard of intervention. Providing the yoga practice should involve movement and concentration. If the movement is correct, even if the intervention is given for only a month, it will show better results. The conclusion of 20 studies systematic literature reviewing yoga interventions has a significant value on reducing fasting blood glucose and cholesterol levels. Yoga practice involves movement and concentration. If the activities are suitable, it shows effective results